Non-linear equation of motion for higher curvature semiclassical gravity - Naman Kumar (Physics Letters B)
We derive the non-linear semiclassical equation of motion for a general diffeomorphism-invariant theory of gravity by leveraging the thermodynamic properties of closed causal horizons. Our work employs two complementary approaches. The first approach utilizes perturbative quantum gravity applied to a Rindler horizon. The result is then mapped to a stretched light cone, which can be understood as a union of Rindler planes. Here, we adopt the semiclassical physical process formulation, encapsulated by 〈Q〉=TδSgen where the heat-flux 〈Q〉 is related to the expectation value of stress-energy tensor Tab and Sgen is the generalized entropy. The second approach introduces a “higher curvature” Raychaudhuri equation, where the vanishing of the quantum expansion Θ pointwise as required by restricted quantum focusing establishes an equilibrium condition, δSgen=0, at the null boundary of a causal diamond. While previous studies have only derived the linearized semiclassical equation of motion for higher curvature gravity, our work resolves this limitation by providing a fully non-linear formulation without invoking holography.